2018
DOI: 10.3846/ijspm.2018.442
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-Based Fis and Anfis Models Development and Comparison for Residential Real Estate Valuation

Abstract: Abstract. There has been an increasing concern on the development of alternative approaches to overcome the problems and deficiencies that occur during the application of real-estate valuation methods. This study was established to investigate the usability of the expert knowledge based fuzzy logic methodology in determining real-estates values. In addition, valuation with the Adaptive Neuro-Fuzzy Inference System (ANFIS) method provided model comparison. Samples were administered a questionnaire for the param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The authors measured the absolute mean error. This revealed a high accuracy of the obtained results and indicated the possibility of using the fuzzy model in property valuations in Turkey (Yalpir, Ozkan, 2018). From this, the first method used to evaluate was the comparative method of market data using statistical inferences and the second method is fuzzy logic.…”
Section: Introductionmentioning
confidence: 65%
“…The authors measured the absolute mean error. This revealed a high accuracy of the obtained results and indicated the possibility of using the fuzzy model in property valuations in Turkey (Yalpir, Ozkan, 2018). From this, the first method used to evaluate was the comparative method of market data using statistical inferences and the second method is fuzzy logic.…”
Section: Introductionmentioning
confidence: 65%
“…, 2008; Belniak and Wieczorek, 2017; Watkins, 1999; Arribas et al. , 2016; Wyatt, 1997; Yalpir and Ozkan, 2018; Liu et al. , 2018b; Abidoye and Chan, 2018a, b; Francke and Vos, 2004).…”
Section: Existing Studies and Challengesmentioning
confidence: 99%
“…Adaptive neuro-fuzzy inference system (ANFIS) integrated the advantages of both neural networks and fuzzy logic systems with high self-adaptability and self learning ability to be identified as a universal estimator for responding to complex problems [16]. The ANFIS was a class of adaptive, multi-layer and feed-forward networks which was comprised of input-output varioubs and a fuzzy rule base of the Takagi-Sugeno type [21].…”
Section: Conceptionmentioning
confidence: 99%
“…In recent years, adaptive neural-fuzzy inference system (ANFIS) combined with both learning and reasoning capability of artificial neural network and fuzzy logic has been developed for solving the complex problems [16]. Akbarpour proposed an ANFIS model to predict the punching shear strength of two-way slabs based on 189 experimental results and found that the proposed model can evaluate the punching load with an acceptable error [17].…”
Section: Introductionmentioning
confidence: 99%